Kinetochore deterioration concommitant with centromere weakening during aging in mouse oocyte meiosis‐I. Issue 5 (20th April 2023) - Yin, Lin; Mihajlović, Aleksandar I.; Yang, Gongshe; FitzHarris, Greg
Abstract: Age‐related oocyte aneuploidy occurs as a result of chromosome segregation errors in female meiosis‐I and meiosis‐II, and is caused by a progressive age‐related deterioration of the chromosome segregation machinery. Here, we assess the impact of age upon the kinetochore, the multi‐protein structure that forms the link between the chromosome and spindle microtubules. We find that in meiosis‐I the outer kinetochore assembles at germinal vesicle breakdown, but that a substantially smaller outer kinetochore is assembled in oocytes from aged mice. We show this correlates with a weaker centromere in aged oocytes and, using nuclear transfer approaches to generate young‐aged hybrid oocytes, we show that outer kinetochore assembly always mirrors the status of the centromere, regardless of cytoplasmic age. Finally, we show that weaker kinetochores in aged oocytes are associated with thinner microtubule bundles, that are more likely to be mis‐attached. We conclude that progressive loss of the centromere with advancing maternal age underpins a loss of the outer kinetochore in meiosis‐I, which likely contributes to chromosome segregation fallibility in oocytes from older females. Abstract : Here we show that oocytes from naturally aged mice assemble a smaller kinetochore in meiosis‐I than oocytes from young mice. Using reciprocal nuclear transfer to separate the impacts of aging upon the nucleus and cytoplasm, we show that it is nuclear aging and not cytoplasmic aging that underpins kinetochore diminution.